Coping strategies of long-term unemployed in Portugal - Suleman, F. (2017)
This paper examines coping strategies adopted by women and men after job loss in Portugal. The data were gathered through interviews and an open-ended inquiry applied to fifteen unemployed persons (eight women), who were asked to describe their cognitive and behavioural efforts to cope with unemployment. Almost all the sampled unemployed persons search for a job, accept or look for training, do odd jobs, or request financial support from family and friends. However, there are interesting differences between women and men. Whereas men find the loss of their breadwinner status difficult, women worry about their economic independence and ultimately gender equality. We suggest that women's early entry in the labour market in Portugal created a social identity based on work, and this identity has contributed to negative consequences of unemployment for both genders. Men and women differ however in their emotions. Men revealed embarrassment, shame but also a colder and rational attitude, while women demonstrated strong emotions including crying during the interview. There are indeed differences in the strategies described by the people interviewed and observed by researchers. Latent strategies enhanced our understanding and therefore represented a powerful source of information.